Preparation of zymosan from yeast cell walls - Holan, Z; Beran, K; Miler, I (Folia microbiologica, 1980)
Cell walls of the yeast Saccharomyces cerevisiae after disintegration and protoplasm removal by centrifugation and repeated washing were suspended in 0.5 M Na2HPO4, pH 7.8-8.0, as a 5% or 10% suspension, depending on the mode of heating. The suspension was boiled for 3 h, purified by repeated washing with water and ethanol and dried. The yield was approximately 1.8% of the starting amount of pressed commercial baker's yeast.
Keywords: metody; Saccharomyces cerevisiae; zymosan; Methods; Zymosan; buněčná stěna; Cell Wall